Usability of 4to24: A Transition Application for Parents of Students With Visual Impairments. (January 2023) - Antonelli, Karla; Steverson, Anne; Cmar, Jennifer L.
Introduction: This article covers the technical development and usability testing of 4to24, a mobile application (app) for students with visual impairments and their parents. The app includes information and resources on numerous topics to support and encourage preparation for employment from an early age.Methods: We partnered with technical developers from the blindness field to design and develop the app using an iterative approach that included usability testing at two key points in the development process. Technical developers incorporated accessibility into the app's design as it was built. Researchers conducted two rounds of usability testing with a total of 9 parents and 10 students. Participants completed specific tasks in the app and completed the System Usability Scale (SUS) to assess the app's usability.Results: Mean SUS scores were 80.83 for Round 1 and 83.75 for Round 2, indicating above-average usability at both time points. In each round, participants provided feedback on the app interface and identified issues impacting the app's ease of use.Discussion: We devised a system that automatically sends relevant informational modules to users based on the student's age, grade level, experience, and progress. The iterative design process allowed us to seek user feedback through usability testing and correct identified issues as development progressed, resulting in an intuitive and easy-to-use app. We also assessed and corrected accessibility issues as they arose, ensuring that the app met users' accessibility needs.Implications for Practitioners: 4to24 is a usable and accessible mobile app that provides parents and students with relevant, timely information and resources to help students prepare for employment as they grow.